2017
DOI: 10.15694/mep.2017.000100
|View full text |Cite
|
Sign up to set email alerts
|

Does the Flipped Classroom improve exam performance in medical education? A systematic review

Abstract: Background: The 'flipped classroom' (FC) is a blended learning model in which educational material is delivered online prior to class, students then apply this knowledge through discussion and problem solving activities in class. Its effectiveness in medical education is debated. The aim of this systematic review is to assess the outcomes of studies which have compared the exam performance of traditional didactic teaching (DT) to the FC in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
(55 reference statements)
3
19
1
Order By: Relevance
“…Our overall findings build on those from several recent systematic (narrative) reviews and meta‐analyses investigating the effectiveness of the FC in health care educational settings. Thus, the systematic narrative reviews reporting mixed findings from individual studies across medical and nursing education typically identified a relatively small number of studies and consistently called for more research and a wider reach in terms of examining the relative efficacy of the FC method across different educational groups . Our meta‐analytical approach was adopted to avoid the subjectivity of the narrative approach to systematic reviews, and to pool the data from a large number of studies to ascertain the relative effectiveness of the FC method across a number of domains …”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Our overall findings build on those from several recent systematic (narrative) reviews and meta‐analyses investigating the effectiveness of the FC in health care educational settings. Thus, the systematic narrative reviews reporting mixed findings from individual studies across medical and nursing education typically identified a relatively small number of studies and consistently called for more research and a wider reach in terms of examining the relative efficacy of the FC method across different educational groups . Our meta‐analytical approach was adopted to avoid the subjectivity of the narrative approach to systematic reviews, and to pool the data from a large number of studies to ascertain the relative effectiveness of the FC method across a number of domains …”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, Chen et al found a varying direction and magnitude of the effect sizes and confidence intervals (CIs) across studies . A more recent systematic review by Hughes and Lyons also found mixed results across 11 studies when considering MCQ outcomes: four studies each demonstrated an advantage and a disadvantage of the FC approach over the LB approach and a further three studies showed mixed results.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations